MASKULINITAS DAN STANDAR KECANTIKAN PADA IKLAN MS GLOW FOR MEN “SEMUA JUGA BISA” - Citra Rani Angga Riswari; Didik Sugeng Widiarto (Jurnal Gesi, 2022)
In Indonesia, the use of facial care products for men is still considered as a taboo. Normalizing the use of facial care products for men is a form of challenge to the concept of toxic masculinity. MS Glow for Men, an Indonesian facial care product especially created for men, has released a video ad titled “Semua Juga Bisa". This video ad became trending topic because of choosing brand ambassador with Stand-up Comedians Babe Cabita and Marshel Widianto who criticed because do not represent the beauty standards in Indonesia. This is MS Glow for Men’s effort to break the beauty standards. This study analyzed Roland Barthes’ the semiotics of communication using Social Construction of Reality Theory. Through the observation the researcher has found that the video ad is against two things, namely masculinity and the beauty standard that is constructed by society. The implementation of those two things above described in the codes in the video ad. Besides that, this study examined the deconstruction of the meaning of male masculinity in the video ad to discuss the myths and ideologies of representation of male masculinity. The researcher also wanted to find the representation of beauty standards in the video ad.